Perbedaan Tingkat Kecemasan Sebelum dan Sesudah Diberikan Terapi Murottal pada Ibu Hamil Trimester III di Puskesmas Jombang - Dian Anggraeni; Sugijati Sugijati; Jamhariyah Jamhariyah (Jurnal Ilmu Kesehatan dan Gizi, 2026)
This study aims to analyze the difference in anxiety levels before and after the administration of Qur’anic murottal therapy among third-trimester pregnant women. The third trimester is often associated with increased physical discomfort and psychological stress, which may lead to higher anxiety levels. This research employed a pre-experimental design using a one-group pretest-posttest approach involving 25 respondents selected through purposive sampling. Anxiety levels were measured using the Perinatal Anxiety Screening Scale (PASS), and the data were analyzed using the Wilcoxon Signed Ranks Test. The findings showed that before the intervention, 48% of respondents experienced moderate anxiety and 52% experienced severe anxiety. After the intervention, 40% experienced mild anxiety, 48% moderate, and only 12% severe anxiety. The statistical test result indicated a Z value of -4.376 with a p-value of 0.000 (p < 0.05), which means there was a significant difference in anxiety levels before and after the intervention. These results suggest that murottal therapy is effective in reducing anxiety among third-trimester pregnant women and can be considered as a safe non-pharmacological intervention.